Strengths, weaknesses, opportunities, and threats analysis on impact of e-learning in biochemistry in phase-I medical undergraduates - Gupta, Preeti (International Journal of Research in Medical Sciences, 2021)
Background: The concept of strengths, weaknesses, opportunities, and threats (SWOT) analysis is to identify advantages, limitations, opportunities, and dangers of e-learning scaffolds in medical education detailed in the field of biochemistry, based upon the perception of stakeholders. It is used to assist faculties in initiating meaningful change in a program and to use the data for program improvement. The aim of the study is to identify, the strength, weaknesses, threats, and opportunities of e-learning of biochemistry to MBBS first-year students. Methods: This educational intervention study was based on an online course, and was conducted at department of biochemistry, L. N. Medical College, Bhopal. 150 students, aged from 18 to 21 years, admitted to the MBBS phase-I, were recruited as a group I and faculties of biochemistry as group II to achieve the objectives of the study. The predesigned open questionnaire was administered to record their perception on e-learning classes. Results: The students and facilitator considered that the online teaching learning is easily accessible and flexibility of time but it also impart feeling of loneliness and unsuitable for skill development program. Though it gives an opportunity of accessibility for higher education for every-one in a very cost effective manner and allow them to balance between their education and job. Conclusions: The online learning is a flexible and assessable teaching learning method but its effectiveness remains subject of discussion. Hence further studies on large scale are required to justify it.